Using Read Encode Annotate And Ponder (Reap) Technique to Increase Reading Comprehension: a Case of the Eleventh Grade Students of SMA Negeri 6 Semarang in Academic Year 2014/2015 - Supriyantini Supriyantini (Universitas PGRI Semarang, 2015)
This final project is aimed for applying Read Encode Annotate and Ponder (REAP) technique for teaching reading comprehension. The objectives of the research are, (1) to find out the students’ reading comprehension after being taught without using REAP technique. (2) to find out the students’ reading comprehension after being taught by using REAP technique. (3) to know whether there is any significant difference of students’ reading comprehension being taught by using REAP technique and without REAP technique. Following the study case the writer used quantitative research. The research design of this study is true experimental design. The sample is the eleventh grade students at SMA Negeri 6 Semarang in Academic Year 2014-2015. There are three classes used, they are the experimental class, control class and a class to be tried out. The writer used test to collect the data. The data was gained from the tests that were given to the students. The study found that the mean score for the class taught without REAP technique was 78.16 and the mean score for the class taught with using REAP technique was 92.05. The students’ score that was taught by using REAP technique was better than students’ score that taught without REAP technique. There was any significant difference between experimental group and control group, because the computation t-test was 7.5. So that is higher than because 7.5 > 2.00. It means that is acceptable and is rejected. Based on the study, it can be concluded that using REAP technique to increase reading comprehension has positive influence to the students. So, English teachers have to use REAP technique to increase the students’ reading comprehension.